Characteristics and impact of aged coal ash with slag emplaced in a karst cave: the case of Divaška jama, Slovenia - Andreea Oarga-Mulec (Nature Portfolio, 2021)
Abstract A mixture of coal bottom ash and slag, with a fraction of fly ash (CAFAS) from steam locomotives, was placed in the cave Divaška jama to delimit and level tourist trails. Emplacement began in 1914 and carried on for several decades. The CAFAS mixed with other cave material gradually changed its structure and appearance. Currently the concentration of some elements in the CAFAS (As, Cu, Hg, Ni, Pb, Zn), and also to a lesser extent in cave sediments (Cr, Cu, Ni), indicates a possibly harmful effect on sediment-associated biota based on ecotoxicological assays. Compared to the cave sediment, the CAFAS contains distinctly different mineral phases and presents a different source of radioactivity. Microbial metabolic activity of CAFAS is low, 0.22 μl O2/gDW h, but higher than that of cave sediment. The present environmental hazards from CAFAS are estimated to be low. Whereas the emplacement of CAFAS was seen initially a long-term solution for waste disposal and management of the cave, it turned out that CAFAS enriches the underground environment with inorganic and organic compounds and disperses pollution into the cave ecosystem. After its removal from the cave, the CAFAS should be investigated thoroughly due to its susceptibility to alteration.